The Tao of Pooh - Hoff, Benjamin, 1946- (New York, N.Y. : Penguin Books, 1983)
Explains the principles of Taoism through Winnie-the-Pooh, and explains Winnie-the-Pooh through the secret wisdom of the Taoists.
Originally published: New York : Dutton, c1982.
Adult
Keywords: Milne, A. A., -- 1882-1956 -- Characters -- Winnie the Pooh; Milne, A. A., -- 1882-1956 -- Religion; Taoism in literature; Taoism; Winnie-the-Pooh (Fictitious character); Milne, A. A. (Alan Alexander), 1882-1956.; Taoism in literature; Taoism; Winnie-the-Pooh (Fictional character)